Could Size Moderate Managerial Ownership, Institutional Ownership, and Audit Quality of Tax Avoidance Occurs in Southeast Asia’s Banking? - Supriyati - Supriyati; Dinda Rahmatur Melyaningrum; Dewi - Murdiawati; Kadek Pranetha Prananjaya (University of Merdeka Malang, 2022)
This study aims to determine the effect of managerial ownership, institutional ownership, and audit quality on tax avoidance and to determine the role of firm size as a moderator in strengthening or weakening the influence of the three independent variables on tax avoidance. The population used in this study is the financial statements and annual reports of banking companies in Southeast Asia which are available on the stock exchange sites of each country and the official websites of related companies in the 2015-2019 period. The sampling technique is used a purposive sampling method with the final result of as many as 144 units of analysis. Analysis of the data used is Multiple Linear Regression Analysis to determine the independent influence variables on dependence and Moderation Regression Analysis to determine the role of moderating variables. The result shows that managerial ownership and audit quality do not affect tax avoidance, while institutional ownership can negatively affect tax avoidance. Moderation analysis shows that firm size can affect independent institutional ownership variables and audit quality on tax avoidance. However, managerial ownership does not affect tax avoidance.